The Doctrine of Manifestation in Fichte’s Principien (1805) - Ivaldo, Marco (Laval théologique et philosophique, 2016)
This article considers the systematic position of Fichte’s Principien (1805), between the philosophia prima that is the Wissenschaftslehre and the specific doctrines of its application ; nature, right, morality, and religion. It considers also the systematic structures of the Principien, with particular attention to the doctrine of manifestation. It does so with sustained attention to the philosophy of religion, since the Principien determines manifestation with respect to the relation between God and world, and the relation between God and world with respect to the doctrine of manifestation.